Il matriarcato slavo Antropologia culturale dei Protoslavi - Gasparini, Evel (Biblioteca di Studi Slavistici, 2010)
This book on Slavic matriarchy is the result of the studies and researches that Evel Gasparini carried out over the span of his lifetime. Intrigued by the possibility of a close link between the collective ownership of the land and the ancient agricultural-matriarchal substrate of Slav culture, Gasparini launched on the titanic enterprise of analysing the archaeological and historical sources of early Slavic civilisation. Basing himself on a concept of culture elaborated in the ethnological field, he brought to light certain contradictions in the application of the Indo-European paradigm to Slavic culture and identified a series of elements illustrating the matriarchal substrate. Exploiting an uncommon knowledge of cultural anthropology and profound linguistic competencies, in this book Gasparini maps out a complex panorama ranging from the economy to the social structure and from the religious traditions to music and dance. Out of print for some time, the book is now proposed in a new, more convenient form, complete with an appendix on Finns and Slavs - which was originally intended as another chapter in the book but was then left out - a detailed preface by Gasparini's disciple Remo Faccani, and a bibliography of the scholar's oeuvre edited by Donatella Possamai.